The level of depression, anxiety, stress and coping strategies in parents with congenital talipes equinovarus children - Awang, Mohd Shukrimi; Abdul Razak, Ardilla Hanim; Azizi, Nurazlina; Bukhori, Nur Amalina Syazwani; Mohamad Zainuddin, Hanisah; Mat Zin, Nora (2017)
A cross-sectional study involving 43 parents with CTEV child was conducted from 18 July till 27 August 2016 at Hospital Tengku Ampuan Afzan. Self-administered Malay version of Depression Anxiety and Stress Scale 21 items (DASS-21)1 is used to measure the psychological wellbeing of the parents and the Malay version of Brief COPE is used to measure coping strategies. There were 43 respondents, majority were Malay (90.7%), female (86%), and married (97.7%). Average age was 30.3 years old. 70% of the respondents were having a positional CTEV child and 30% have structural CTEV. Overall, prevalence of depression, anxiety, and stress among parents were very low. Only 9.3% experience depression, 11.6% experience anxiety, and only 2.3% was reported to be stress. The psychological wellbeing of the parents was not related with the parental age, gender, marital status, education level, and monthly income. The most common coping strategy used is religion, acceptance and positive reinterpretation.